Betuletol, a Propolis Component, Suppresses IL-33 Gene Expression and Effective against Eosinophilia - Aurpita Shaha; Rezwanul Islam; Naonobu Tanaka; Yoshiki Kashiwada; Hiroyuki Fukui; Noriaki Takeda; Yoshiaki Kitamura; Hiroyuki Mizuguchi (Molecules, 2022)
Propolis, a resinous substance produced by honeybees, has been used in folk medicine since ancient times due to its many biological benefits such as antitumor, antioxidant, antimicrobial, anti-inflammatory, and immunomodulatory effects. Propolis contains flavonoids, terpenoids, aromatic aldehydes, and alcohols, which vary with different climate and environmental conditions. In our study, we examined the antiallergic activity of Brazilian green propolis (BGP) and isolated the active compound that can suppress an allergy-sensitive gene, IL-33, expression and eosinophilia. Ethanolic extract of BGP freeze-dried powder was fractionated with several solvent systems, and the active fractions were collected based on activity measurement. The single active compound was found by thin-layer chromatography. Using column chromatography and NMR, the active compound was isolated and identified as 3,5,7-trihydroxy-6,4’-dimethoxyflavone, also known as betuletol. Further, the antiallergic activity of that has been examined in PMA-induced up-regulation of IL-33 gene expression in Swiss 3T3 cells. Our data showed the IL-33 gene suppression both by BGP and the isolated active compound, betuletol. We also found that betuletol suppressed ERK phosphorylation, suggesting it could be effective in suppressing IL-33 mediated eosinophilic chronic inflammation and will provide new insights to develop potent therapeutics against allergic inflammations.